Reclaiming the Narrative: A Critical Discourse Analysis of Donald Trump's 2024 Super Tuesday Campaign Speech - Tito Dimas Atmawijaya (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This study critically analyzes Donald Trump's 2024 campaign speech using Fairclough's Critical Discourse Analysis (CDA) framework to explore how his rhetorical strategies construct power relations and reinforce ideological divisions. By examining key rhetorical devices such as pronouns, metaphors, hyperbole, and Repetition, the study reveals how Trump's language fosters a collective identity among his supporters, positioning them as defenders of "true" American values. The analysis also demonstrates how Trump employs a problem-solution structure to portray himself as the sole solution to issues like immigration, economic instability, and national security. The study further contextualizes Trump's rhetoric within broader discursive practices, showing how the speech resonates with populist themes of institutional distrust and nationalism. By drawing on socio-cultural trends such as the rise of populism and media fragmentation, Trump effectively mobilizes his base while deepening ideological divides. The "us versus them" narrative, a hallmark of populist discourse, is examined in light of Fairclough's and van Dijk's theories, highlighting the role of language in shaping social realities and power dynamics. Through this analysis, the research aims to shed light on the broader implications of political discourse in maintaining and challenging power structures within a divided society.